The THE INFLUENCE OF SERVANT LEADERSHIP AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE THROUGH EMPLOYEE RESILIENCE IN THE NANGGALO DISTRICT OFFICE, PADANG CITY: PENGARUH SERVANT LEADERSHIP DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI MELALUI RESILIENSI PEGAWAI DI LINGKUNGAN KANTOR CAMAT NANGGALO KOTA PADANG - Silva Andani Prita, Silva; Yeni, Fitri; Charli, Chintya Ones (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This study aims to analyze the influence of servant leadership and work motivation on employee performance through resilience at the Nanggalo District Office, Padang City. The issue of employee performance, as indicated by attendance rates, lateness, and fluctuating achievement of work targets, highlights the need for a managerial approach based on servant leadership and strengthened work motivation. This research employs a quantitative approach with data collection techniques using questionnaires and documentation for the employees of the Nanggalo District Office. The independent variables in this study are servant leadership (X1) and work motivation (X2), the dependent variable is employee performance (Y), and employee resilience (Z) serves as the intervening variable. The results show that servant leadership and work motivation have a positive and significant effect on employee resilience. In addition, servant leadership, work motivation, and resilience also directly and significantly influence employee performance. Resilience is proven to be a mediating variable that strengthens the influence of servant leadership and work motivation on employee performance. These findings emphasize the importance of servant leadership, high work motivation, and resilience in improving employee performance, particularly within local government bureaucracy. Therefore, efforts to improve employee performance should focus on strengthening servant leadership, providing motivation, and developing resilience on an ongoing basis.